Socialisation musicale, frontières culturelles et sociabilités urbaines. Les parcours des personnes immigrantes d'origine maghrébine à Montréal - Marcoux-Gendron, Caroline (Institut national de la recherche scientifique, 2021)

Musiciens migrants d'origine arabe dans le contexte montréalais : le parcours de la reconnaissance - Marcoux-Gendron, Caroline (Université de Montréal, 2015)

Parcours professionnels de musiciennes migrantes : de la théorie à l'expérience. Note de terrain à propos du colloque Femmes musiciennes du monde tenu les 26 et 27 novembre 2021 au Centre des musiciens du monde - Marcoux-Gendron, Caroline; Champagne, Lysandre (La Revue musicale OICRM, 2022)

Mapping as a Complementary Perspective on the Dynamics of Participation in a City’s Musical Life - Marcoux-Gendron, Caroline; De Alvarenga, Bernardo (Bulletin of Sociological Methodology/Bulletin de Méthodologie Sociologique, 2020)
Maps and map-making have been used in a range of research about musical phenomena in cities. Yet, most of these studies focus on musicians; few have attempted to understand how people take part in a city’s musical life in terms of event attendance. Likewise, little has been said about the attendance habits of immigrants, despite the quick transformation of urban populations due to the expansion of human migration. Approaching a subject that has received so little attention as the dynamics of participation of immigrants in a city’s musical life therefore requires an inventive research design. Building from a methodology combining semi-structured interviews and observation, I used maps and map-making to deepen the analysis of North African immigrants’ cultural practices in Montreal. Trying to give a spatial legibility to their musical activities in the city generated many technical and theoretical concerns, but was also helpful for reflecting on the project differently and highlighting some characteristics of the data that were not obvious from the initial fieldwork. In brief, maps and map-making proved to be efficient complementary tools to ethnography, bringing new insights and raising new queries about the practices being considered.
Keywords: audiences; cartes; cartographie; cities; cultural participation; cultural practices; ethnographie; ethnography; immigration; map-making; maps; music; musique; participation culturelle; pratiques culturelles; publics; villes

Socialisation musicale et sociabilités urbaines. Parcours de personnes immigrantes originaires d'Afrique du Nord à Montréal - Marcoux-Gendron, Caroline (L'interculturel contemporain au carrefour des disciplines, 2021)